2016
DOI: 10.5194/aab-59-19-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perch availability on performance, carcass characteristics, and footpad lesions in broilers

Abstract: Abstract. In the modern broiler industry, solutions are still being sought to improve conditions or eliminate problems related to issues such as animal welfare, health, and meat quality brought by intensive production systems. Therefore, this experiment was conducted to study effects of perching on growth performance, carcass characteristics, and footpad lesions (FPLs) in broiler chickens. A total of 300 broiler chicks (Ross 308) were distributed into control and perch groups with three replicates including eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Use of such structures may strengthen muscles and joints and enhance the blood supply to the legs, wings and heart [17]. Their provision has been associated with greater tibial diaphysis diameter [18], a reduction in tibial dyschondroplasia [19], reduced severity of footpad dermatitis [20], lower mortality due to heat stress [21], and a lower heterophil to lymphocyte ratio [22, 23]. Peat moss is an environmental enrichment material that stimulates ground scratching and dustbathing behaviour [24, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…Use of such structures may strengthen muscles and joints and enhance the blood supply to the legs, wings and heart [17]. Their provision has been associated with greater tibial diaphysis diameter [18], a reduction in tibial dyschondroplasia [19], reduced severity of footpad dermatitis [20], lower mortality due to heat stress [21], and a lower heterophil to lymphocyte ratio [22, 23]. Peat moss is an environmental enrichment material that stimulates ground scratching and dustbathing behaviour [24, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are typically still intensive but require some combination of lower stocking densities, natural light, perches, straw bales and/or pecking devices. Although biologically relevant for poultry, the typical bar perches provided in broiler housing are poorly used and do not appear to improve many welfare parameters (LeVan et al, 2000;Bailie and O'Connell, 2015;Kiyma et al, 2016). Recently, several studies have revealed that broilers show a preference for platform style perches, which require less balancing and are more suitable for their heavy conformation (Norring et al, 2016;Bailie et al, 2018;Malchow et al, 2018).…”
mentioning
confidence: 99%
“…Recently, several studies have revealed that broilers show a preference for platform style perches, which require less balancing and are more suitable for their heavy conformation (Norring et al, 2016;Bailie et al, 2018;Malchow et al, 2018). Introducing perches that attract a high level of use may benefit broilers by satisfying a natural motivation, encouraging more diverse motor patterns in young birds and reducing the time they spend in contact with wet litter, which could improve leg health and severity of contact dermatitis (Ventura et al, 2010;Kiyma et al, 2016;Kaukonen et al, 2017a,b). Natural roosting behaviour also allows for extended periods of undisturbed rest and can reduce the levels of fearfulness in a commercial house (Yngvesson et al, 2018;Baxter et al, 2019).…”
mentioning
confidence: 99%
“…This indicates that the hens learn perch use and better use vertical space with time. The tendency to increase use of perches with age was also shown in broilers [ 23 ] and young layers without prior perch experience [ 20 ]. Similar to perch use, hens from both lines showed an ability to learn to use nests, decreasing the percent of floor eggs over time, with slopes varying between tests from − 4.89 to − 3.32% per week for L1 and from − 3.53 to − 2.47% for L2.…”
Section: Resultsmentioning
confidence: 94%